The Analysis Office Facility Management Strategy at Pt X - Ni Made Krisma Dwi Yuliati; Christian Wiradendi Wolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Office facility management plays a crucial role in supporting operational activities, ensuring employee productivity and comfort. This study analyzes the management strategies employed by the General Affairs Division at PT X, focusing on facility planning, asset maintenance, workspace organization, and evaluation processes. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. Results reveal that while facility management improves operational efficiency and workspace utilization, challenges such as budget limitations and dynamic operational needs persist. Recommendations include implementing preventive maintenance schedules and adopting digital tools like Computerized Maintenance Management Systems (CMMS).